Bimetallic Fe–Co catalysts for the one step selective hydrogenation of CO2 to liquid hydrocarbons. Issue 5 (3rd February 2023) - Wang, Wei; Toshcheva, Ekaterina; Ramirez, Adrian; Shterk, Genrikh; Ahmad, Rafia; Caglayan, Mustafa; Cerrillo, Jose Luis; Dokania, Abhay; Clancy, Gerard; Shoinkhorova, Tuiana B.; Hijazi, Nibras; Cavallo, Luigi; et al.
Abstract : K-promoted Fe–Co bimetallic catalysts fabricated by a straightforward sol–gel approach exhibited outstanding catalytic performance for one step selective hydrogenation of CO2 into high value-added liquid hydrocarbons with C10 –C20 linear α-olefins. Abstract : The direct conversion of CO2 to value-added products has received considerable attention as it can effectively mitigate CO2 emission and alleviate over-reliance on fossil fuels. We report the synthesis of a series of K-promoted Fe–Co bimetallic catalysts along with their performance for the selective hydrogenation of CO2 to liquid hydrocarbons (mostly linear α-olefins (LOAs)). High dispersion of K and Co on the catalysts was achieved through a modified one pot sol–gel approach. Both K and Co significantly influence catalyst activity and selectivity. By systematically studying the adsorption energies of key reactants on modeled iron oxide and carbide surfaces by density functional theory, we demonstrate that addition of K increases the affinity of the catalyst towards the adsorbed species. On the other hand, the presence of Co facilitates the spontaneous dissociation of H2 . As a result of the high dispersion of components achieved through the one pot synthesis, at 300 °C, 20 bar (H2 /CO2 = 2) and 7200 mL gcat. −1 h −1, the optimized catalyst exhibits a C5 + space time yield of 15.8 mmol gcat. −1 h −1 along with a C5 + selectivity of 51% at a CO2 conversion of 35%.